Exploring Division-I Student-Athletes’ Memorable Messages From Their Anticipatory Socialization. - Cranmer, Gregory A.; Myers, Scott A. (Communication Quarterly)
This study explored the socialization of 118 Division-I student-athletes via the topics of memorable messages that they received prior to their arrival on campus. Ten topics were identified (i.e., desirable attitudes, hard work, physical skill or ability, opportunities, pride, inclusion, challenges, athletes as symbols, the importance of education, and the duration of college athletics) using first cycle coding and were subsequently categorized as either addressing the characteristics or experiences of collegiate student-athletes using second cycle coding. These findings continue to demonstrate that characteristics and experiences associated with roles are prevalent within athletes’ memorable messages but also highlight the inherent ambiguity and the contradictions regarding how to use these messages and balance the dual roles of being a student-athlete. This study provides a novel communicative lens for understanding athlete socialization but underscores the need to recognize receivers’ processing and application of memorable messages.